Importing pancreata for transplantation: a single-center experience across evolving allocation eras - Tamburrini, Riccardo; Hidalgo, Stacey; Leverson, Glen; Kaufman, Dixon B.; Neidlinger, Nikole A.; Al-Adra, David P.; Aufhauser, David D.; Thiessen, Carrie; Mandelbrot, Didier; Parajuli, Sandesh; Odorico, Jon S. (Frontiers in Transplantation, 2025)
Recent changes to allocation systems have increased the geographic distribution of pancreas offers, often originating from outside a transplant center's donor service area or region. The impact of this wider sharing on outcomes remains uncertain. This study analyzed outcomes of primary pancreas transplants (2000–2018) at a large transplant center, stratified retrospectively on the nautical miles distance from the donor hospital. Primary endpoints were death-censored graft survival (DC-GS), patient survival, and graft thrombosis at different time points. No significant differences were found in DC-GS or patient survival for recipients of simultaneous pancreas-kidney (SPK), pancreas after kidney (PAK), or pancreas transplant alone (PTA), regardless of the distance from the donor hospital to the transplant center. Thrombosis rates were comparable across groups. Imported pancreata were from younger donors with lower BMI compared to locally recovered grafts. These findings support the notion that importing pancreata for transplantation is a feasible and safe practice that benefits patients, increases organ utilization, while benefiting transplant center volume data and reducing waiting times for patients. Encouraging wider importation may reduce waiting times and improve access to pancreas transplantation.